Detection of Human Bocavirus in Children Suffering from Respiratory Tract Infection in Diyala Province - Taha Yaseen, Zaid; Kh Khudair, Mohammed; S Naseef, Asmaa; I Alezzi , Jalil (Diyala Journal of Medicine, 2020)
Background: Human Boca virus (HBoV) is one of the viral infections present worldwide. Objective: To determine the role of HBoV in respiratory tract infection. Patients and Methods: Cross sectional study consists of 160 (Pharyngeal secretions and blood ) samples were collected from children who attended Al-Zahraa Hospital for respiratory complaints during the period from October 1st 2018 to April 30th 2019, including both genders and ages ranging from (3 months to 10 years). The samples were divided into two groups. First group consisting of (80) blood samples for patients, while the second group (80) sample swabs from the pharynx. Results: The prevalence of HBoV using PCR technique was 38.3%. Those less than 2 years showed the highest rate of infection 43.5%, followed by 5-7 years 42.9% and 2-4 years 33.3% while the lowest percentage in the age group (8-10 years) 28.5%. A high rate of IgG was recorded in age group less than 2 years old 51.3%, followed by the category of 5-7 and 2-4 years with 28.6% and 22.2% respectively. Conclusion: A high rate of HBoV infection in children with respiratory illness in Diyala province.